2014 IEEE International Conference on Communications Workshops (ICC) 2014
DOI: 10.1109/iccw.2014.6881170
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse shaping on bit error rate performance and out of band radiation of Generalized Frequency Division Multiplexing

Abstract: Generalized Frequency Division Multiplexing (GFDM) is a multicarrier transmission scheme that offers flexible pulse shaping of individual subcarriers. The application of pulse shaping per subcarrier can control the out of band (OOB) radiation and create non-orthogonal waveforms. In this paper, the influence of the pulse shaping to the overall system performance, namely bit error rate (BER) over AWGN channels and OOB radiation, is investigated. Closed from expressions for the BER and power spectral density (PSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 10 publications
0
68
0
2
Order By: Relevance
“…This is an interesting counterintuitive result, because the interference introduced by the MF with RC is composed by ISI and ICI, while the RRC is a Nyquist pulse and thus creates only ICI [14].…”
Section: Metric To Evaluate Synchronization Errorsmentioning
confidence: 95%
See 2 more Smart Citations
“…This is an interesting counterintuitive result, because the interference introduced by the MF with RC is composed by ISI and ICI, while the RRC is a Nyquist pulse and thus creates only ICI [14].…”
Section: Metric To Evaluate Synchronization Errorsmentioning
confidence: 95%
“…For instance, Figure 10 exhibits the influence of the MF receiver with raised cosine (RC) and root-raised cosine (RRC) [14] as a function of the roll-off parameter α, assuming perfect synchronization.…”
Section: Metric To Evaluate Synchronization Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data transmission on each block is distributed in time and frequency and each sub-carrier is pulseshaped. Reduction of OOB emission is obtained in GFDM by using different time-domain pulse shaping filters other than the conventional rectangular one used in CP-OFDM [18]. Moreover, the tail biting technique used in GFDM makes the CP length to be independent of transmit and receive filters length [16].…”
Section: Introductionmentioning
confidence: 99%
“…Methods for the cancellation of self-interference with a MF receiver have been proposed in [19], where it is shown that almost equal performance as orthogonal MCM can be achieved. The same MF receiver is considered in [18] to study the impact of different pulse shaping filters on OOB and error rate performance.…”
Section: Introductionmentioning
confidence: 99%